Insecticidal Effects of Blue Ternate (Clitoria Ternatea) Leaf Extract Against Mosquito Wrigglers - Anamarie Valdez; Hassanal Abusama; Nikoshi Lapuz; Samantha Martinez; Stephanie Pineda; April Tolentino (ASEAN Journal of Science and Engineering, 2021)
The purpose of conducting this research is to determine the effectiveness of blue ternate (Clitoria Ternatea) leaf extracts for terminating mosquito wrigglers by making a mosquito larvae insecticide. To determine the effectiveness of the leaf extract to terminate mosquito wrigglers, a mortality test was conducted. The numbers of the dead mosquito wrigglers were checked every 5 min. The results showed that the blue ternate leaf is effective to eliminate mosquito wriggler and the amount of leaf extract in the ethanol brings different effectiveness. The present study showed that both ethanolic extract and pure leaf extract of Clitoria Ternatea are effective as insecticidal against mosquito wrigglers. The insecticidal effects of Clitoria Ternatea against mosquito wrigglers will contribute largely to the people, to help those people who cannot afford to buy insecticide and to lessen the number of people who encounter diseases caused by mosquitoes.